Sanguinarine, Isolated From Macleaya cordata, Exhibits Potent Antifungal Efficacy Against Candida albicans Through Inhibiting Ergosterol Synthesis - Hu, Ziwei; Hu, Hao; Hu, Zhili; Zhong, Xiaojun; Guan, Yifu; Zhao, Yunshi; Wang, Lu; Ye, Liang; Ming, Liliang; Riaz Rajoka, Muhammad Shahid; He, Zhendan; Wang, Yan; et al. (Frontiers in Microbiology, 2022)
In recent decades, infections caused by the opportunistic fungus Candida albicans have increased, especially in patients with immunodeficiency. In this study, we investigated the mechanism of action of sanguinarine (SAN) against C. albicans both in vitro and in vivo. SAN exhibited antifungal activity against C. albicans clinical isolates, with MICs in the range of 112.8–150.5 μM. Furthermore, scanning electron and transmission electron microscopy showed that SAN induced morphological changes as well as structure disruption in C. albicans cells, including masses of cellular debris, ruptured cell walls, and membrane deformation. Flow cytometry revealed that SAN could lead to cell membrane damage, and ergosterol content analysis indicated that SAN could cause ergosterol content reduction exceeding 90%. Further, we validated the efficacy of SAN against candidiasis caused by C. albicans in a murine model, and SAN significantly improved survival and reduced weight loss compared to vehicle. The treatment of 1.5 and 2.5 mg/kg/d SAN obviously reduced the fungal burden in the kidney. In addition, histopathological examination indicated that no fungal cells were observed in lung and kidney tissues after SAN treatment. Hence, this study suggests that SAN is a promising plant-derived compound for the development of an effective anticandidal agent.